Challenges and opportunities in embedding core components of substance use health care into Housing First programs - Oluwaseyi Dolapo Somefun; Vicky Stergiopoulos; Sheena Taha; Nick Kerman; Leslie Buckley; Natalie Aubin; Alexander Caudarella; Stephanie Caroline Juhasz; Karly Muriel McCrone; Jodie Millward; Tomas Mirabelli; Kim Corace (Frontiers in Public Health, 2026)
Background The intersecting crises of homelessness and substance use health (SUH) harms require a critical re-evaluation of mental health, SUH, and social care integration. Housing First (HF) is an evidence-based approach to ending chronic homelessness, but challenges in effectively supporting individuals with significant SUH needs within the intervention have not been well-documented. A national pan-Canadian workshop convened multidisciplinary partners to identify barriers, opportunities, and core components for the successful integration of SUH care within HF programs. Methods The workshop involved a diverse group of attendees ( n = 59), including direct service providers, people with lived and living experience (PWLLE), healthcare professionals, community leaders, researchers, and policymakers. Following brief presentations on key topics, a series of structured breakout sessions were conducted. Discussions were centred on two primary issues: (1) the key challenges and opportunities for integrating SUH care in HF programs, and (2) the core components and strategies required to advance the use of SUH best practices within HF. Results Qualitative data collected from the breakout sessions revealed four key challenges: (1) fragmented services; (2) workforce challenges; (3) restrictive policy and funding environments; and (4) stigma. Opportunities for integration included: (1) strategic alignment; (2) cross-sector collaboration; (3) equity-informed use of data; and (4) flexible model adaptation. Core components for effective SUH integration in HF programs were identified as: (1) person-centred and flexible approaches; (2) foundational support for the workforce; and (3) integrated and collaborative care systems. Conclusion Effectively integrating SUH care into HF requires a fundamental shift toward more person-centric systems: flexible, low barrier, culturally safe models that organize housing, health, harm reduction, treatment, recovery, peer, and community supports around individuals' self defined goals. The findings underscore the urgent need for coordinated policy action, grounded in evidence and lived expertise, to create a responsive system that upholds the right to both housing and health.